Allocation of liability for dangerous goods under international trade law : CIF and FOB contracts - Gelgec, Ahmet (London [England] : Hart Publishing, 2022)
"This book explores the allocation of risk and liability of dangerous goods between the seller and the buyer under CIF (Cost, Insurance and Freight) and FOB (Free on Board) contracts, providing an in-depth study of the issue of carriage of dangerous goods in the context of international trade law. In addition to offering specific solutions to issues arising in the context of the contract of sale, the book provides a non-contractual angle, putting forward suggestions under non-contractual mechanisms. Importantly, the book incorporates case law examples from the Commonwealth and the US. Dangerous goods that are carried by sea carry with them potential risks of losses and damages to the vessel, other cargoes and lives on board. The allocation of liability arising out of the carriage of dangerous goods has recently attracted unwelcome attention because of mis-declared cargoes leading to fires on board ships. Thus the book fills a gap in the literature by addressing the issue in detail with examples from multiple jurisdictions, and proposing solutions. In particular, the book analyses whether and to what extent the law of international sale of goods can provide any assistance in the re-allocation of liability between the buyer and the seller. This book will be of great interest to all those involved in the research as well as legal practice of international trade law and carriage of goods by sea law."--
1. Introduction -- 2. Types of Dangerous Goods Part I: General -- 2. General Framework of Liability for Dangerous Goods -- 3. The Shipper and Its Liability under CIF and FOB Contracts Part II: Methods of Liability Transfer -- 4. Transfer of Liability from the Seller to the Buyer under Contract -- 5. Other Mechanisms for Imposition of Liability Part III: Remedies -- 6. Causal Link under the Contract Of Sale -- 7. Recovery of the Loss under the Contract -- 8. Non-Contractual Remedies -- 9. Conclusion
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Liability for hazardous substances pollution damages; Hazardous substances -- Law and legislation; Freight and freightage -- Law and legislation; Electronic books